2005
DOI: 10.1136/bjo.2004.048074
|View full text |Cite
|
Sign up to set email alerts
|

The preoperative intraocular pressure level predicts the amount of underestimated intraocular pressure after LASIK for myopia

Abstract: Aims: To evaluate the statistical significance of the parameters that affect underestimation of intraocular pressure (IOP) after laser in situ keratomileusis (LASIK) for myopia. Methods: In this prospective case series study, patient age, axial length, preoperative corneal curvature, preoperative central corneal thickness (CCT), preoperative IOP, and ablation depth were studied to determine whether they affect the underestimation of IOP in the right eyes of 100 consecutive patients who underwent LASIK. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…Thus, preoperative IOP measured by rebound tonometry could help predict the amount of IOP decrease after LASIK. 2 Although rebound tonometry is significantly correlated with CCT in normal eyes 7,26 and in eyes with glaucoma, [9][10][11][12]27 multivariate analyses found that the corneal biomechanical properties of corneal hysteresis (CH) and the corneal resistance factor (CRF) play a more significant role in rebound tonometry. 7,28 Corneal biomechanics are also important contributing factors that affect IOP measurement with other tonometers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, preoperative IOP measured by rebound tonometry could help predict the amount of IOP decrease after LASIK. 2 Although rebound tonometry is significantly correlated with CCT in normal eyes 7,26 and in eyes with glaucoma, [9][10][11][12]27 multivariate analyses found that the corneal biomechanical properties of corneal hysteresis (CH) and the corneal resistance factor (CRF) play a more significant role in rebound tonometry. 7,28 Corneal biomechanics are also important contributing factors that affect IOP measurement with other tonometers.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 To prevent misdiagnosing an eye with glaucoma as being normal because of an artificially low IOP finding, accurate IOP measurement is important in patients having LASIK, particularly in a population with a high prevalence of myopia. 3 The gold standard for IOP measurement is Goldmann applanation tonometry.…”
mentioning
confidence: 99%
“…Certain surgical procedures, and a series of corneal diseases, are associated with substantial changes in the corneal tissue structure, and prospectively with altered biomechanical properties [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…1 An association between primary open-angle glaucoma and myopia has been reported. 2 Accordingly, IOP evaluation is important for evaluating myopic patients after LASIK.…”
mentioning
confidence: 99%